Association Between Dietary Habits And Anaemia Among Pregnant Adolescents Attending Antenatal Care Clinics In The Upper East Region - Hamid, A.K. (University Of Ghana, 2020)
The purpose of this study was to determine the prevalence of anaemia in pregnant adolescent girls (10-19 years of age) and dietary habits that affect this condition. This study also assessed the knowledge of the pregnant girls in the Upper East Region of Ghana. An analytical cross-sectional study design was employed between January and October 2020. A multistage sampling technique was used to identify the districts, health facilities and in the selection of study participants. In all, 331 pregnant adolescent girls were interviewed using a modified Food Frequency Questionnaire (FFQ). Capillary blood samples were taken from each respondent to test for anaemia using a portable HemoCue 301 analyser. The collected data was cleaned, coded, and entered in Microsoft Excel 2016 and exported to STATA Version 15 for analysis. Frequencies and proportions were reported whiles associations between selected variables were explored using the Pearson’s chi-square test at a significance level of P <0.05 at a 95% confidence interval. A total of 331 pregnant adolescent girls from ages 13 – 19 years with a mean age of 17.94 ± 1.12 years took part in this study. The gestational ages of the pregnancies ranged from 8weeks to 42 weeks with the mean being 26.08±6.77 weeks. Anaemia prevalence based on the WHO classification for Haemoglobin (HB) concentration in the blood states that, for a pregnant woman, concentrations of less than 11.0g/dl indicates anaemia. Laboratory test done on the girls indicated that anaemia was high (65.86%). Moderately anaemic (HB less than 11.0g/dl to 7.0g/dl) girls were 34.14 % whiles 0.91% were severely anaemic (HB less than 7.0g/dl). Consumption of meat (p<0.001), poultry (p=0.001), fish (p<0.001), liver (p<0.001), eggs (p=0.007), vegetables (p<0.001), fruits (p<0.001), legumes (p<0.001), tea (p=0.001), sweet beverages (p<0.001) and local juices (p<0.001) were found to be statistically associated with the prevalence of anaemia among the pregnant adolescent girls interviewed at the univariate level. However, at the multivariate level when all the factors were put in a model, consumption of meat (OR = 0.40; 95% CI [0.17, 0.88]), fish consumption (OR = 0.15; 95% CI [0.04, 0.51]), fruit consumption (OR = 0.35; 95% CI [0.13, 0.95]) and bread consumption (OR = 0.06; 95% CI [0.01, 0.62]) were found to be associated with anaemia prevalence. Meat and Fish consumption were found to be protective against contracting anaemia when consumed. Knowledge on the causes, prevention, and complications of anaemia as well as the good sources of iron was generally high. However, knowledge of anaemia treatment strategies was low. The findings of this study suggest that education of pregnant women should be an ongoing initiative to raise awareness and enhance compliance with supplementation. Complementary interventions such as fortification, dietary diversification, and the reduction of infections may also need to be scaled up to ensure that diverse iron sources are consumed as well as minimize iron losses. These findings are of significance to public health practitioners in their efforts directed at the prevention of anaemia in the Upper East Region and Ghana as a whole.
MPH
Keywords: Dietary Habits; Anaemia; Pregnant Adolescents; Upper East Region; Antenatal Care Clinics